2006
DOI: 10.1007/s00467-006-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Daily urinary interleukin-11 excretion correlated with proteinuria in IgA nephropathy and lupus nephritis

Abstract: Interleukin-11 (IL-11) is a multifunctional cytokine with both thrombopoietic and anti-inflammatory effects. In an animal study IL-11 was shown to reduce proteinuria in mice with necrotizing glomerulonephritis. The purpose of this current study is to explore the role of IL-11 in human glomerulonephritis. Subjects of this study were patients with proteinuria (daily urine protein excretion >40 mg/m2 per hour) and underlying pathology of IgA nephropathy (IgAN) (n=20), lupus nephritis (LN) (n=40), and idiopathic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…Although a possible imbalance in Th1/Th2 proinflammatory cytokines release has been reported to play a pivotal role in the pathogenesis of immunocomplex-mediated glomerulonephritis [2][3][4][7][8][9], there is little information on Th1 or Th2 predominance in HSPN. With respect to Th1/Th2 predominance in IgA nephropathy, a model of IgA nephropathy in ddY mice has been reported to show strong polarization toward Th1 in the early stage of the disease [5].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although a possible imbalance in Th1/Th2 proinflammatory cytokines release has been reported to play a pivotal role in the pathogenesis of immunocomplex-mediated glomerulonephritis [2][3][4][7][8][9], there is little information on Th1 or Th2 predominance in HSPN. With respect to Th1/Th2 predominance in IgA nephropathy, a model of IgA nephropathy in ddY mice has been reported to show strong polarization toward Th1 in the early stage of the disease [5].…”
Section: Discussionmentioning
confidence: 98%
“…Although the pathogenesis of HSPN remains to be elucidated, presumptive inflammatory reactions due to predominant immunoglobulin A (IgA) deposition in the mesangium is thought to play a pivotal role, similar to its role in IgA nephropathy [1]. The results from recent studies suggest the possible role of an imbalance in Th1/Th2 proinflammatory cytokines in the development and progression of glomerulonephritis, including IgA nephropathy [2][3][4][5]. However, to the best of our knowledge, there is little information on Th1 or Th2 predominance in HSPN.…”
Section: Introductionmentioning
confidence: 96%
“…The significance of the TI compartment in LN disease has been a topic of much interest, and, for many years, authors have suggested that examination of the TI compartment might be useful for predicting outcome in LN [6,26]. Recently, studies of urinary biomarkers in LN kidney injury suggest that biomarkers may play a role in diagnosis and risk stratification of kidney damage [24,[27][28][29]. Presumably, biomarkers of tubular injury would correlate more highly with a TI index than a glomerular index [28,29]; but whether this is true is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggest that an imbalance between Th1 and Th2 cells might be associated with the development and progression of several forms of glomerulonephritis [2,3]. Most patients with LN or IgAN are thought to exhibit Th1/Th2 heterogeneity; however, no clear evidence of this exists [4][5][6]. Rengarajan et al reported that the relative predominance of T-bet or GATA-3 may determine Th1/Th2 polarization [7].…”
Section: Introductionmentioning
confidence: 96%